On the Naming of Methods: A Survey of Professional Developers - Alsuhaibani, Reem; Newman, Christian; Decker, Michael; Collard, Michael; Maletic, Jonathan (Proceedings / International Conference on Software Engineering, 2021)
This paper describes the results of a large (+1100 responses) survey of professional software developers concerning standards for naming source code methods. The various standards for source code method names are derived from and supported in the software engineering literature. The goal of the survey is to determine if there is a general consensus among developers that the standards are accepted and used in practice. Additionally, the paper examines factors such as years of experience and programming language knowledge in the context of survey responses. The survey results show that participants very much agree about the importance of various standards and how they apply to names and that years of experience and the programming language has almost no effect on their responses. The results imply that the given standards are both valid and to a large degree complete. The work provides a foundation for automated method name assessment during development and code reviews.